Proposta de um algoritmo para o problema de roteirização do transporte escolar rural - Prata, Priscila de Almeida (2009)
Rural School Transportation is a very important topic but which is scarcely discussed in academic papers, mainly the routing of vehicles for this transport. Its importance is due to the fact that is a constitutional right and results in huge expenses to the municipalities that are responsible for the biggest part of them. Treating this problem manually, like in many Brazilian cities, and considering every one of the system s particularities is a complex task. In this context, the Geographic Information Systems (GIS) constitute a convenient Decision Support Tool, but the algorithms that are incorporated in them are not adequate for treating the problem which results in solutions unviable in practice. On the other hand, some GIS permit the inclusion of new functionalities, by means of programming languages, so that the routines may be adapted to the user s needs. Thus, this research proposes an algorithm for the definition of routes that generates more practical solutions. The algorithm is used by a tool where the users inform the necessary data for the definition of the routes and the outcome is a report and a map with the routes. It is also possible to consult each of the routes individually. The algorithm and the tool were developed in TransCAD using a programming language called GIDDK (Geographic Information System Developer s Kit). In order to analyze the performance of the algorithm, two case studies were developed for Brazilian cities with different characteristics. The results showed that the algorithm and the tool may be used as a Decision Support Tool for the definition of rural school transportation routes.